1997
DOI: 10.1038/42755
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Overview of the yeast genome

Abstract: The collaboration of more than 600 scientists from over 100 laboratories to sequence the Saccharomyces cerevisiae genome was the largest decentralised experiment in modern molecular biology and resulted in a unique data resource representing the first complete set of genes from a eukaryotic organism. 12 million bases were sequenced in a truly international effort involving European, US, Canadian and Japanese laboratories. While the yeast genome represents only a small fraction of the information in today's pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(118 citation statements)
references
References 0 publications
1
115
1
1
Order By: Relevance
“…Our conclusion is obviously contradictory to that of the yeast genome project (Mewes et al, 1997). According to their map, ATP3 and YBR030W are single-copy genes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our conclusion is obviously contradictory to that of the yeast genome project (Mewes et al, 1997). According to their map, ATP3 and YBR030W are single-copy genes.…”
Section: Discussioncontrasting
confidence: 99%
“…The nuclear genes encoding the F 1 sector subunits are all single-copy genes, according to the yeast genome project (Mewes et al, 1997). However, it has been found that ATP1 (Takeda et al, 1995(Takeda et al, , 1999 and ATP2 (Takeda, personal (Ohnishi et al, 2003) is a duplicate gene.…”
Section: Introductionmentioning
confidence: 99%
“…The entire genome of S. cer6isiae has been sequenced and all genes, of both known and putative function, have been identified (19). At present, cDNA arrays containing the complete set of 6,144 open reading frames (ORFs) for S. cer6isiae have been constructed, with only about 25% having a known function.…”
Section: An Example Of Things To Come: Sacchromyces Cervisiaementioning
confidence: 99%
“…Saccharomyces cerevisiae was the first eukaryote whose genome was completely sequenced (Mewes et al, 1997;Goffeau et al, 1996). Chromosome III, the first eukaryotic chromosome to be completed, was a landmark in the field of genomic sequencing (Oliver et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The initial gene annotation of S. cerevisiae was based on identification of open reading frames (ORFs) of more than 100 amino acids (Mewes et al, 1997) and on prediction of introns using the well established splicing rules for this fungus (Brian and Micheal, 1992). The 100 amino acid size cut-off was picked in order to avoid fortuitous ORFs (Termier and Kalogeropoulos, 1996).…”
Section: Introductionmentioning
confidence: 99%